Legal Review of the Liability Framework for Remote Sensing by Looking at the Global Navigation Satellite System (GNSS) - Talei, Simin Asadzadeh; Bouzari, Sepideh; Bagheri, Sakineh (Jurnal Cita Hukum, 2019)
Abstract:Compensation for losses in the law is certain and the civil liability system is designed to respond to this need. Nowadays, it is necessary to check compensation in different fields, and specialists in each field are seeking data to recognize liability issues and even reduce the risk of liability in their work. The legal recognition of the subject is necessary because the field of remote sensing and mapping is one of the fields with many activists and plays an important role in various aspects of the life of the community, but many people still do not have any data about their rights, and even those involved in this field as producers or consumers do not have legal data on this issue, and due to the involvement of this data in the lives of individuals and the existence of relevant cases in the judiciary. Therefore, the accurate recognition of this issue will cause questions in this field to be answered in law. And lawyers and judges can also rely on the recognition and analysis of this issue to avoid error and work more efficiently. Keywords: Liability, Remote Sensing, Fault, Global Navigation Satellite System (GNSS)Abstrak:Kompensasi untuk kerugian dalam hukum merupakan kepastian, dan sistem pertanggungjawaban sipil dirancang untuk menanggapi kebutuhan ini. Saat ini, perlu untuk memeriksa kompensasi di bidang yang berbeda dan spesialisasi di setiap bidang, guna mencari data untuk mengetahui masalah pertanggungjawaban, selain mengurangi risiko pertanggungjawaban dalam pekerjaan mereka. Pengakuan hukum atas subjek diperlukan, karena bidang penginderaan jauh dan pemetaan adalah salah satu bidang dengan banyak aktivis dan memainkan peran penting dalam berbagai aspek kehidupan masyarakat, walaupun masih banyak orang yang tidak memiliki data tentang hak mereka. Bahkan mereka yang terlibat dalam bidang ini sebagai produsen atau konsumen tidak memiliki data hukum tentang masalah ini, disebabkan karena keterlibatan data ini dalam kehidupan individu dan adanya kasus yang relevan dalam peradilan. Oleh karena itu, pengakuan yang akurat atas masalah ini akan menimbulkan pertanyaan pada permasalahan ini dan dijawab secara hukum. Pengacara dan hakim juga dapat mengandalkan pengakuan dan melakukan analisis terhadap masalah ini untuk menghindari kesalahan dan bekerja lebih efisien.Kata kunci: Pertanggungjawaban, Penginderaan Jauh, Kesalahan, Global Satellite Satellite System (GNSS) Аннотация:Компенсация за ущерб определена законом, и система гражданской ответственности разработана в ответ на эту потребность. В настоящее время необходимо изучить вопрос компенсации в различных областях и специализации в каждой области в целях поиска данных для выяснения вопроса об ответственности, а также снизить риск ответственности в своих работax. Юридическое признание рассматриваемого лицанеобходимо, потому что область дистанционного зондирования и картографирования является одной областью со многими действующими лицами и играет важную роль в различных аспектах общественной жизни, хотя все ещё есть много людей, которые не имеют данных о своих правах. Даже те, кто вовлечён в эту область в качестве производителей или потребителей, не имеют правовых данных по этому вопросу из-за вовлечения этих данных в жизнь отдельных лиц и наличия соответствующих дел в судебной системе. Таким образом, точное признание этой проблемы поднимет вопросы, которые будут решены юридически. Адвокаты и судьи также могут рассчитывать на признание и анализ проблемы, чтобы избежать ошибок и работать более эффективно.Ключевые Слова: Ответственность, Дистанционное Зондирование, Ошибки, Глобальная Навигационная Спутниковая Система (Гнсс)